Imagining the post-fossil city: why is it so difficult to think of new possible worlds?. Issue 2 (3rd April 2019) - Hajer, Maarten; Versteeg, Wytske
ABSTRACT: The phenomenon of climate change requires a rethinking of existing socio-geographical arrangements. This paper argues that the transition to 'post-fossil urbanization' is hampered by the lack of positive imaginations of alternative possible urban futures and post-fossil city life. It asks the question why it is so difficult to conceive of new possible urban worlds, and tries to answer it by using the established concept of 'imaginary' and introducing the concept of 'technique of futuring'. The salience of the imaginary of the modern city is used as an example. The paper points at the International Society for Organization (ISO) and 'living labs' as contemporary techniques of futuring, organizing urban futures. It then aims to recoup one's capacity to imagine alternative possible worlds and explores the role that academics can play in this endeavour.